The numerical field calculation in structures with the space-uniform quadruple focusing by the method of auxiliary charges - Tishkin, S.S. (Вопросы атомной науки и техники, 2001)
In the paper the procedure of solving integral equations with the use of auxiliary charges is used. The electrostatic field potential is presented in the form of superposition of the fields of point sources located out of the investigated region at some distance from it. The values of N charges are determined from the boundary conditions at N points of the boundary. The definition of the point sources is equivalent to using some function of the charge density at the boundary of the region. This approach was used for the calculation of structures with the space-uniform quadruple focusing with sinusoidal and trapezoidal modulation, and also a section of the transverse matching of the “funnel”.